Large negative thermal expansion in non-perovskite lead-free ferroelectric Sn2P2S6. Issue 8 (8th February 2016) - Rong, Yangchun; Li, Menglei; Chen, Jun; Zhou, Mei; Lin, Kun; Hu, Lei; Yuan, Wenxia; Duan, Wenhui; Deng, Jinxia; Xing, Xianran
Abstract : Here, we firstly demonstrate the ferroelectrostriction (SVFS) mechanism in a non-perovskite lead-free ferroelectric Sn2 P2 S6 for its large negative thermal expansion. Abstract : Functional materials showing both negative thermal expansion (NTE) and physical performance, such as ferroelectricity and magnetism, have been extensively explored in the past decade. However, among ferroelectrics a remarkable NTE was only found in perovskite-type PbTiO3 -based compounds. In this work, a large NTE of −4.7 × 10 −5 K −1 is obtained in the non-perovskite lead-free ferroelectric Sn2 P2 S6 from 243 K to T C (338 K). Structure refinements and first-principle calculations reveal the effects of the Sn(ii ) 5s–S 3p interaction on spontaneous polarization and its correlation with NTE. Then the mechanism of spontaneous volume ferroelectrostriction (SVFS) is verified and it could well elucidate the nature of NTE in ferroelectric Sn2 P2 S6 . This is the first case to demonstrate the unusual NTE behavior by SVFS in a non-perovskite lead-free ferroelectric material.